FKKT Navdih Znanosti - Slemnik, Mojca; Kravanja, Zdravko; Novak Pintarič, Zorka (2019)
FCCE Inspired by Science. The brochure contains all of the FCCC's essential information, faculty vision, study programs, access requirements, student activities, course syllabuses and labs presentations: employees, research areas, the most important achievements, updated the most important publications, cooperation with institutions and companies, ongoing projects and research equipment.
Keywords: Faculty of Chemistry and Chemical Engineering; UM; The mission of the faculty; Presentation of laboratories; Study programs; Course syllabus